2001
DOI: 10.1001/jama.285.21.2743
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme Replacement Therapy in Fabry Disease

Abstract: Intravenous infusions of alpha-gal A are safe and have widespread therapeutic efficacy in Fabry disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
897
1
41

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 1,197 publications
(969 citation statements)
references
References 28 publications
10
897
1
41
Order By: Relevance
“…Recently, clinical trials have shown that enzyme replacement with recombinant human a-galactosidase A can increase a-galactosidase A levels, decrease endothelial inclusions, and improve pain symptoms. 16,17 However, enzyme replacement therapy costs approximately $160 000 annually. 4 Thus, with this now readily available but expensive therapy, it is imperative for clinicians to be aware of the rare patient whose Fabry-like syndrome is iatrogenically induced and who does not require a-galactosidase A replacement.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, clinical trials have shown that enzyme replacement with recombinant human a-galactosidase A can increase a-galactosidase A levels, decrease endothelial inclusions, and improve pain symptoms. 16,17 However, enzyme replacement therapy costs approximately $160 000 annually. 4 Thus, with this now readily available but expensive therapy, it is imperative for clinicians to be aware of the rare patient whose Fabry-like syndrome is iatrogenically induced and who does not require a-galactosidase A replacement.…”
Section: Discussionmentioning
confidence: 99%
“…Two of these trials (TKT003 and extension 12 and TKT005 and extension) 13 were singlecenter phase II trials, and one was a multicenter phase III trial (TKT010 and extension).…”
Section: Clinical Trial Designs and Treatmentsmentioning
confidence: 99%
“…Numerous clinical trials, observational studies, and registry data have provided some evidence for the safety and efficacy of ERT in improving disease symptoms, cardiac mass, renal function, and quality of life Schiffmann et al 2001;Weidemann et al 2003;Wilcox et al 2004;Banikazemi et al 2007;Hughes et al 2008;Koskenvuo et al 2008;Imbriaco et al 2009;Mehta et al 2009;Feriozzi et al 2012). To date, there have been limited comparisons of the two agents, from which no firm conclusion can be drawn regarding their relative efficacy and safety (Lidove et al 2010).…”
Section: Introductionmentioning
confidence: 99%